FORMS AND FEATURES OF EDUCATIONAL MODELLING - Mkrtchyan, Kristina; Mnatsakanyan, Lusine (Foreign Languages for Special Purposes, 2024)
The purpose of the article is to present the importance of modeling in teaching. In the article the general types of models are examined. The concept of modeling, the connection between the concepts of modeling and design, the modeling functions are distinguished. The significance of the use of modeling in practical teaching is great, which can be realized through the study of its functions.